Modeling of the Drying Kinetics of Slurry Droplet in Spray Drying - Boris Golman (ASEAN Journal of Chemical Engineering, 2011)
The detail analysis of the heat and mass transfer between the droplet containing suspended solids and the drying gas was carried out numerically. The temperature and moisture distributions within the slurry droplet were calculated during the first and second drying phases. The parametric study revealed that the droplet drying time decreases with increasing the drying gas temperature and decreasing the droplet diameter.